STUDI LIVING QURâAN TERHADAP AMALAN IBU HAMIL DI KECAMATAN BERUNTUNG BARU KABUPATEN BANJAR - Isnawati, Isnawati (Faculty of Ushuluddin and Humanities, 2015)
Along with the times, study the Koran and Hadith experiencing developments study area, from the study ofÂ texts to the socio-cultural studies, which is then referred to as âliving Koranâ and âliving traditionâ. In addition,Â living study the Koran that not only the existence of textual, but a social phenomenon that was born linked toÂ the presence of the Koran in a specific geographic region and specific future anyway. However, the phenomenonÂ appears not always directly proportional to what is supposed to be practiced and in amalkan. Seeing thisÂ phenomenon the author tries to do more research about reading (practice) of the Koran in public District ofÂ Lucky New Banjar Regency, the authors wanted to uncover the sura and verse what is used as a bidder, healerÂ or medicine that mamampu cure physically and mental reserved for pregnant women. Any problems with theÂ formulation of sura and verse of the Koran that used pregnant women, and then what are the factors that affectÂ pregnant women mengamlkan suras and verses of the Koran in the District of New Lucky Banjar district.